A true PML approach for steady-state vibration analysis of an elastically supported beam under moving load by a DLSFEM formulation. (15th October 2020) - Froio, Diego; Rizzi, Egidio; Simões, Fernando M.F.; da Costa, António Pinto
Highlights: Unitary and robust implementation for numerical steady-state response of infinite beam on elastic foundation under transverse moving load. Original derivation of a new, effective Perfectly Matched Layer (PML) technique to simulate far-field conditions for fourth-order beam problem. Discontinuous Least-Squares FEM (DLSFEM) implementation for fourth-order beam problem. Extensive numerical validation and consistent comparison to existing analytical solution. Comprehensive numerical outcomes on physical beam response in the whole parametric space. Abstract: This paper concerns a computational implementation for solving a Moving Load (ML) problem on an infinite Euler–Bernoulli elastic beam on a Pasternak visco-elastic support. A steady-state dynamic response in convected coordinate is sought, by a numerical approach with discretization over a finite domain, implying spurious boundary reflections of non-evanescent waves. This is effectively solved by: (a) analytically formulating a new, true Perfectly Matched Layer (PML) approach, toward handling the underlying fourth-order differential problem and the corresponding far-field conditions, without adopting special boundary conditions; (b) outlining a local Discontinuous Least-Squares Finite Element Method (DLSFEM) formulation, apt to provide a robust approach for the present non self-adjoint problem and to conveniently handle the jump condition in the shear force at the concentrated ML position. Consistent numerical results are illustrated and compared to an available analytical solution, showing a perfect match, with a complete removal of spurious boundary effects and a proof of theoretical a priori error estimates. Further results are produced for a case with multiple MLs. The paper shows that the present innovative DLSFEM-PML formulation is effectively suitable to numerically solve a steady-state ML problem on an infinite beam, setting up a new computational tool in such a challenging mechanical context.